Challenges and experience of the Ethiopian rural health extension program: Implications for reform and revitalization - Zerfu, Taddese Alemu; Tareke, Amare Abera; Biadgilign, Sibhatu (BioMed Central, 2023)
Background Despite remarkable gains over the past decade, mounting evidence suggests that Ethiopia’s rural health extension program (HEP) is facing serious implementation challenges. We investigated the current and potential future program design and implementation challenges of Ethiopia’s rural HEP based on the lived experiences of health extension workers (HEW) implementing the program at the grassroots level. Methods We employed a longitudinal qualitative exploration linked to a larger cluster-randomized trial (RCT) which was implemented in 282 villages randomly selected from 18 Kebeles of the Gedeo zone, southern Ethiopia. Data were collected using in-depth interviews with key informants, focus group discussion, and passive observation of program implementation. The data were analyzed manually using a thematic framework analysis approach. Themes and sub-themes were generated by condensing, summarizing, and synthesizing data collected in the field in the form of extended notes and field observation checklists. Findings Despite considerable gains in availing basic health services to the rural population, HEP seems to suffer serious design and implementation flaws that demand thoughtful and immediate adjustment. The design constraints span from the number and type of intervention packages to the means of dissemination (vehicle) as well as the target population emphasized. As such, some low-cost high-impact interventions that were strongly desired by the community were overlooked, while others were inappropriately packed. The means of distribution - female health extension workers trained with basic prevention skills, were lacking essential skills. They also had high burnout rates and with little engagement with men, were repeatedly mentioned flaws of the program demanding revitalization. Furthermore, the sheer structure of HEP precluded adult and adolescent men, non-reproductive women, and the elderly. Conclusion Despite significant gains over the last couple of months, Ethiopia’s rural HEP appears to have reached a tipping point that requires a comprehensive revamp of the program package, means of distribution, and target beneficiaries rather than the “usual” tweaks to reap maximum benefits.